2013
DOI: 10.1007/s12032-013-0789-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-139 targets CXCR4 and inhibits the proliferation and metastasis of laryngeal squamous carcinoma cells

Abstract: Our previous studies have showed that chemokine receptor 4 (CXCR4) was over-expressed in laryngeal squamous cell carcinoma (LSCC). However, the mechanism underlying aberrant CXCR4 expression remains unclear. To investigate the roles played by miRNAs in CXCR4 over-expression in LSCC, putative miR-139 was predicted through computational algorithms, including TargetScan, PicTar and miRBase, and luciferase reporter assay was explored to confirm that whether CXCR4 was directly regulated by miR-139. Then, quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…Additionally, miR-139 suppresses epithelial-mesenchymal transition, migration and invasion in hepatocellular carcinoma, and the incidence and severity of pulmonary metastasis in orthotopic liver tumors in mice is also reduced (20,27). Furthermore, Zhang et al (28) revealed that colorectal cancer cell viability, colony formation, nude mice tumor growth, cell migration and invasion are repressed by miR-139, and Luo et al (29) demonstrated that proliferation, invasion and metastasis of laryngeal squamous carcinoma cells are also reduced. miR-139 functions as a tumor suppressor in esophageal squamous cell carcinoma by cell proliferation, migration and invasion inhibition, apoptosis induction and G0/G1 phase cell cycle arrest (22).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-139 suppresses epithelial-mesenchymal transition, migration and invasion in hepatocellular carcinoma, and the incidence and severity of pulmonary metastasis in orthotopic liver tumors in mice is also reduced (20,27). Furthermore, Zhang et al (28) revealed that colorectal cancer cell viability, colony formation, nude mice tumor growth, cell migration and invasion are repressed by miR-139, and Luo et al (29) demonstrated that proliferation, invasion and metastasis of laryngeal squamous carcinoma cells are also reduced. miR-139 functions as a tumor suppressor in esophageal squamous cell carcinoma by cell proliferation, migration and invasion inhibition, apoptosis induction and G0/G1 phase cell cycle arrest (22).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, mir-139 is silenced in a number of solid tumors including hepatocellular carcinomas, gastric and metastatic breast cancers, laryngeal squamous cell carcinoma or glioma. 29,[38][39][40] Different mir-139 targets or pathways were proposed, which might explain the reduction of metastasis and tumor progression by mir-139, such as ROCK1, NOTCH1 (Notch-signaling), TCF4 (Wnt-pathway), CXCR4 or anti-apoptotic MCL1. 10,38,[41][42][43] Here, we described a mechanism, which might broadly explain the cell cycle inhibitory and pro-apoptotic effect of mir-139 in a wide range of neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…29,[38][39][40] Different mir-139 targets or pathways were proposed, which might explain the reduction of metastasis and tumor progression by mir-139, such as ROCK1, NOTCH1 (Notch-signaling), TCF4 (Wnt-pathway), CXCR4 or anti-apoptotic MCL1. 10,38,[41][42][43] Here, we described a mechanism, which might broadly explain the cell cycle inhibitory and pro-apoptotic effect of mir-139 in a wide range of neoplastic cells. By integrating proteomics data, global gene expression profiling and miRNA-target prediction algorithms, we show that mir-139 globally controls the cellular protein synthesis rate by targeting EIF4G2, an essential component of the translation initiation complex consisting of EIF4E, EIF4G and EIF4A.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biomarkers are believed to be beneficial not only in evaluating the prognosis but also in guiding personalized therapy for patients with cancer [3,4]. Therefore, it is necessary to search for potential biomarkers of human LSCC.…”
Section: Introductionmentioning
confidence: 99%